Graphical chain models / Wan Fauzi Wan Mamat - Wan Mamat, Wan Fauzi (Universiti Teknologi MARA, Pahang, 1996)
This article is to show the GUM (Statistical package) approach in use, as viewed by the working statistician. One modem approach is to consider initially only those models which can be understood purely in terms of conditional independence relationship. This is made attractive through the simple graphical characterisation of such models given by Darroch, Lauritzen and Speed (1980). GraphicaI models are easily interpreted in terms of conditional independence relation.